2011
DOI: 10.1186/cc9973
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the value of pre-hospital tracheal intubation: an all time systematic literature review extracting the Utstein airway core variables

Abstract: IntroductionAlthough tracheal intubation (TI) in the pre-hospital setting is regularly carried out by emergency medical service (EMS) providers throughout the world, its value is widely debated. Heterogeneity in procedures, providers, patients, systems and stated outcomes, and inconsistency in data reporting make scientific reports difficult to interpret and compare, and the majority are of limited quality. To hunt down what is really known about the value of pre-hospital TI, we determined the rate of reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 103 publications
1
46
0
Order By: Relevance
“…However, the clinical significance of this remains unclear as the number of intubation attempts is not associated with pneumonitis or mortality [16]. Hypoxia and hyperventilation have been shown to have negative effects on outcome in traumatic brain injury patients undergoing prehospital RSI [17], but are rarely reported [18]. One recent study of anaesthetists performing prehospital RSI in Scandinavia found that desaturation occurred in 10.9% of patients [11].…”
Section: Introductionmentioning
confidence: 97%
“…However, the clinical significance of this remains unclear as the number of intubation attempts is not associated with pneumonitis or mortality [16]. Hypoxia and hyperventilation have been shown to have negative effects on outcome in traumatic brain injury patients undergoing prehospital RSI [17], but are rarely reported [18]. One recent study of anaesthetists performing prehospital RSI in Scandinavia found that desaturation occurred in 10.9% of patients [11].…”
Section: Introductionmentioning
confidence: 97%
“…Variability in patient populations, disease state, comorbidities, injury or illness severity, provider level-of-training and experience, intubation protocols, procedure performance, response/scene/transport intervals, use of neuromuscular blocking agents and sedatives, equipment, and disposition all likely affect outcomes but are inconsistently reported, as the present report demonstrates [1]. …”
mentioning
confidence: 99%
“…Data was not routinely available in this prehospital cohort about airway and ventilation management after intubation, potential downstream complications of prehospital airway management, and hospital-based patient outcome following endotracheal intubation attempts. The optimal set of prehospital and hospital measures to assure high-quality airway management has not been fully defined; future research should evaluate the usefulness of different elements of a proposed Utstein-style template for the uniform reporting of prehospital airway management (34, 35). The airway registry was populated with self-reported data from paramedics performing the advanced airway procedures.…”
Section: Discussionmentioning
confidence: 99%